2012
DOI: 10.1016/j.bpj.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Early Afterdepolarization-Mediated Triggered Activity in Cardiac Monolayers

Abstract: Early afterdepolarizations (EADs) are voltage oscillations that occur during the repolarizing phase of the cardiac action potential and cause cardiac arrhythmias in a variety of clinical settings. EADs occur in the setting of reduced repolarization reserve and increased inward-over-outward currents, which intuitively explains the repolarization delay but does not mechanistically explain the time-dependent voltage oscillations that are characteristic of EADs. In a recent theoretical study, we identified a dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
9
27
0
Order By: Relevance
“…This feature can be clearly seen in Fig.32b. This behavior was also demonstrated in an experimental system in a recent study [324], which shows that the frequency decreases during the oscillations (Fig.32c). …”
Section: Nonlinear Dynamics In Single Myocytessupporting
confidence: 79%
See 1 more Smart Citation
“…This feature can be clearly seen in Fig.32b. This behavior was also demonstrated in an experimental system in a recent study [324], which shows that the frequency decreases during the oscillations (Fig.32c). …”
Section: Nonlinear Dynamics In Single Myocytessupporting
confidence: 79%
“…Recent studies [166, 253, 322324] have developed a nonlinear dynamical theory for EADs and showed that EADs arise from a dual Hopf-homoclinic bifurcation, and that chaos is responsible for the irregular appearance of EADs. This theory is summarized in the following sections.…”
Section: Nonlinear Dynamics In Single Myocytesmentioning
confidence: 99%
“…S2 C) If voltage quickly decays into window voltage for oscillations and then outward current increases very slowly through the Hopf-homoclinic bifurcation window, a very long EAD burst can result. As demonstrated in our previous simulations (57), the slow accumulation of [Na] i causing a very slow increase of I NaK can be a candidate for finally terminating the long-lasting EAD burst.…”
Section: Mechanisms Of Complex Ead Patternssupporting
confidence: 52%
“…For example, [Na] i accumulates very slowly, causing a very slow increase in I NaK , which can also initiate the Hopf-homoclinic bifurcation, as shown in our previous simulations (57). Late I Na is another candidate because it may slowly inactivate (58).…”
Section: Mechanisms Of Complex Ead Patternsmentioning
confidence: 53%
See 1 more Smart Citation